Optimasi Strategis Kebijakan Pemilahan Sampah Rumah Tangga di Kota Ambon Menggunakan Importance-Performance Analysis (IPA) dan Matriks SWOT: Indonesia - Rumakat, Abdul Asis; Widyarsana, I Made Wahyu (UII, 2026)
Waste sorting remains a major challenge in implementing the Reduce-Reuse-Recycle (3R) principles in Ambon City, with only 18,16% participation annually. This study aims to develop a strategic model to improve waste sorting in Ambon City through Importance-Performance Analysis (IPA) and SWOT matrix analysis. The methodology employed includes Confirmatory Factor Analysis (CFA) to derive loading factors and mean scores from a Likert scale 1-5 questionnaire. IPA analysis was used to identify key indicators, which were synthesized into SWOT factors. The analysis revealed that each SWOT variable had varying numbers of indicators and different weightings, with the highest weight attributed to Attitude (5,802), followed by Subjective Norm (3,426), Information Intervention (2,688), Perceived Behavioral Control (2,682), Regulations and Policies (2,340), and the lowest to Facility Support (1,186). Indicators with the highest weightings were prioritized in formulating household waste sorting policies in Ambon. The findings indicate that the most optimal policy direction includes fostering positive attitudes towards waste segregation, strengthening pro-soring social norms, enhancing information interventions, providing simple sorting guidelines, reorienting regulatory and policy functions, and developing centralized waste sorting facilities. This study provides a strategic framework for the Ambon City government to enhance waste management practices while reducing dependency on landfill.